Traveling Realisms, Shared Modernities, Eternal Moods: The Uses of Anton Chekhov in Nuri Bilge Ceylan's Winter Sleep. (12th March 2019) - Mathew, Shaj
Abstract: Nuri Bilge Ceylan's Turkish drama Kış Uykusu / Winter Sleep (2014) owes an enormous debt to nineteenth-century Russian realism. This article explains why Ceylan looks to Russia through an analysis of the film's form and the historical context that binds Russia and Turkey. By placing Turkish and Russian realism on the same plane, this article complicates the asymmetrical binary of East/West that is frequently upheld by analyses of 'Eastern' rewritings of 'Western' literary classics. Instead it offers a more equitable model of international exchange, a nonhierarchical relationship of not East/West but East and East.